Gedung Pameran Otomotif Di Surabaya Automotive Exhibition Building in Surabaya - Amy, Amy Novianingtyas; Feri Hermawan Muslim (WASTU: Jurnal Wacana Sains & Teknologi, 2025)
The automotive world as a means of self-actualization and hobby. For such automotive hobbyist communities, the cars or motorcycles supplied may not necessarily meet their tastes. So the existence of automotive hobbyists creates a new market for car or motorcycle entrepreneurs. The targeted market and the one that still survives today is the imported car market. The existence of a representative automotive center in Surabaya or can be called the Automotive Exhibition Building can be a forum for hobbyists and business people interested in the automotive field. Automotive Exhibition Building facilities in Surabaya such as workshops and showrooms are still separated, making it difficult for people who want practicality and convenience. On this basis, an automotive center that not only functions as a showroom and workshop but also as a sale of accessories and car maintenance items was built in Surabaya.